Klasifikasi Penyakit Kulit Menggunakan Algoritma Naïve Bayes Berdasarkan Tekstur Warna Berbasis Android - Furqan, Mhd.; Nasution, Yusuf Ramadhan; Fadillah, Rini (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The Skin is an important part of the human body which is used to protect organs from external disturbances (radiation, heat, sharp objects, etc.). the surface of the skin is divided into several textures, namely soft, rough, and supple. The skin also stores fat and is supple. The skin also stores fat and nerves which help in the process of human senses, the skin can also experience bacterial interference that can cause disease, the easiest thing to identify affected skin is through visuals (images). This research is to implement the naive bayes algorithma to classify android based skin diseases in helping the identification process of skin diseases based on visual form (color). Based on the results of the study that the classification of skin diseases (eczema, acne, chicken pox, etc). can be indentified through the naive bayes method and can obtain an accuracy of 75%.